Reticulated platelets predict cardiovascular death in acute coronary syndrome patients - Cesari, Francesca; Marcucci, Rossella; Gori, Anna Maria; Caporale, Roberto; Fanelli, Alessandra; Casola, Giulia; Balzi, Daniela; Barchielli, Alessandro; Valente, Serafina; Giglioli, Cristina; Gensini, Gian Franco; Abbate, Rosanna (Thrombosis and Haemostasis, 2013)
Reticulated platelets (RP) are newly-formed platelets with a greater mass, a residual amount of RNA and an increased prothrombotic potential. No studies investigating the association between RP and the risk of cardiovascular death in acute coronary syndrome (ACS) patients are available. In the frame of the AMI-Florence 2 study, we investigated RP in 229 (154 M/ 75 F) ACS patients (125 ST-elevation myocardial infarction [STEMI]; 104 Non-STEMI/Unstable Angina). RP were measured by using the Sysmex XE-2100 haematology analyzer and were expressed as the percentage of RP out of the total optical platelet count (immature platelet fraction; IPF) and as the percentage of RP highly fluorescent (H-IPF). At one-year follow-up, 22 out of 229 patients (9.6%) died from cardiovascular causes. Higher values of IPF (p=0.05) and H-IPF (p=0.006) were detected in dead compared to alive patients. A receiver operating characteristics curve analysis identified IPF ≥3.3% and H-IPF ≥0.9% as optimal cut-off values to predict cardiovascular death. At the multivariate model adjusted for the Global Registry of Acute Coronary Events (GRACE) risk score, the association between RP and cardiovascular death remained significant for both IPF [OR (95%CI) : 4.15 (1.24–13.91) p=0.02] and H-IPF [OR (95%CI): H-IPF 5.03 (1.38–18.38) p=0.01]. In conclusion, RP are independent predictors of cardiovascular death and may be useful in improving risk stratification for ACS patients. Future prospective studies to evaluate the role of RP in determining cardiovascular events are warranted.
Keywords: Acute coronary syndrome; cardiovascular death; platelet turn-over; reticulated platelets